Diferenças culturais nacionais e as respostas socioambientais das empresas do setor de papel e celulose frente à covid-19 - Merlin, Higya Alessandra (2022)
Evoking the origin of legitimacy in institutional theory, it is understood that environmental and sociocultural pressures are relevant in the behavior of organizations. Thus, in the environment of the pulp and paper sector, and considering the covid-19 pandemic, this study aimed to analyze whether national cultural aspects influenced the disclosure of CSR by companies in the pulp and paper sector in the face of the crisis caused by the pandemic. covid-19. The specific objectives were: to measure the socio-environmental disclosure carried out by companies in the pulp and paper sector before and after the beginning of the covid-19 pandemic; verify the socio-environmental practices evidenced by companies in the pulp and paper sector specifically in response to the covid-19 pandemic; and to correlate the cultural dimensions of Hofstede (DCH) and the socio-environmental disclosure of companies in the pulp and paper sector in each country before the pandemic and after the beginning of the covid-19 pandemic. Data was collected in CSR reports regarding the 2019 and 2020 practices of 21 different companies located in Brazil, Canada, the United States and Sweden. In light of the Theory of Legitimacy and DCH, the approach was qualitative and quantitative. To this end, socio-environmental disclosure (DSA) was measured as a dependent variable, and DCH were chosen as independent variables. The hypotheses were tested by panel regression and comparison of means. Descriptive statistics showed that Brazilian companies were the ones that most publicized their socio-environmental actions and responses to the covid-19 pandemic. The environmental category was the most publicized by all countries, while commitments to employees were the most publicized in responses to the pandemic. As for DCH, there was a negative and significant relationship between DSA and individualism and indulgence, and a positive and significant relationship linked to great distance to power and great aversion to uncertainty. No statistical significance was found regarding masculinity and long-term orientation. Regarding the difference in average socio-environmental disclosure between 2019 and 2020, by groups, considering each DCH, there was a statistically significant difference for all variables, with the exception of long-term orientation. The findings allow us to position the study as a contribution to increasing the theoretical framework related to covid-19 in the business area, as well as for the basis of managerial decisions more aligned with the cultural differences of each society.